230k views
5 votes
Simplify the expression:
(10x2 -1 + 4x) + (3 + 5x2 - 4x)

1 Answer

2 votes

Answer:


\boxed{\sf 15x^2 + 2}

Explanation:

Simplify the expression:


\sf \implies(10 {x}^(2) - 1 + 4x) + (3 + 5 {x}^(2) - 4x)

Grouping like terms, 10x² + 5x² + 4 x - 4 x - 1 + 3 = (10 x² + 5x²) + (4 x - 4 x) + (-1 + 3):


\sf \implies (10 x^2 + 5 x^2) + (4 x - 4 x) + (-1 + 3)

10x² + 5x² = 15x²:


\sf \implies 15 x^2 + (4 x - 4 x) + (-1 + 3)

3 - 1 = 2:


\sf \implies 15 x^2 + (4 x - 4 x) + 2

4 x - 4 x = 0:


\sf \implies 15 x^2 + 2

User Rashmi
by
5.6k points